Nitric Oxide, Peroxynitrite, Peroxynitrous Acid, Nitroxyl, Nitrogen Dioxide, Nitrous Oxide: Biochemical Mechanisms and Bioaction - Kovacic, Peter; Somanathan, Ratnasamy (Current Bioactive Compounds, 2012)
This review deals with nitrogen oxides (NO, NO2, N2O) and NO derivatives peroxynitrite, peroxynitrous acid and nitroxyl, in relation to therapeutic effects and toxicity. An important member is NO which plays a multiple role in physiological action. The derivatives formed from interactions with superoxide are powerful oxidants functioning in toxicity. Nitroxyl (HNO), a metabolite of hydroxamic acids and hydroxyurea, is involved in the mode of action. Antioxidant action is discussed, as well as cell signaling. A multifaceted approach to bioaction is recommended.
Keywords: cell signaling